Shared Experience Workshop and the Impact of the Centre for Hidden Histories Research Projects - Allwork, Larissa (The University of Nottingham, 2016)
On 19th September 2016, academic and community participants in research projects funded by the Centre for Hidden Histories convened for a ‘Shared Experience Workshop’ at Derby Riverside Centre. The day was organised by Impact Fellow, Dr Larissa Allwork, Community Liaison Officer, Mike Noble and Principle Investigator on the Centre for Hidden Histories project, Professor John Beckett. Participants presented their findings and discussed their experiences of working as part of an AHRC Connected Communities First World War Engagement Centre.